Foraminiferal Evidence of Late Holocene Sea-Level Change and Amerindian Site Distribution at Montague Harbour, British Columbia - Reinhardt, Eduard; Easton, Norman; Patterson, R. (Géographie physique et Quaternaire, 1996)
ABSTRACTForaminiferal and sedimentological analysis of an underwater stratigraphie section from an Amerindian habitation site at Montague Harbour, British Columbia has further documented late Holocene sea level changes. It appears that part of the documented transgression was caused by tectonic subsidence of the area (Event 1 at approx. 3500 calendar years BP and Event 2 sometime before 1100 calendar years BP) and was recognized in the stratigraphie record by rapid environmental changes. The environmental changes caused by rapid shifts in water depth were recognized through sedimentological and foraminiferal evidence. The tectonic subsidence events, coupled with gentle late Holocene transgression, caused the breaching of Montague Harbour's northwestern channel. The breaching of the channel improved water circulation and increased salinity within the harbour. The salinity changes are reflected in the shift from a low salinity Cribroelphidium excavatum (Terquem, 1876) phenotype "clavata" dominated biofacies (1) at the base of the section to a higher salinity Buccella tenerrima (Bandy, 1950) and Elphidiella hannai (Cushman and Grant, 1927) dominated biofacies (2) at the top. These sea-level changes would have eventually forced local Amerindian settlements inland. The 14C dating of wood and shell, indicates that the recovery of archaeological remains of the Charles culture (ca.6500-3200 years BP) requires investigation in deeper waters.